1111 'Pause, power up, push on' – positivity in the pandemic. (17th August 2022) - Mooncey, Mumtaz; Pal-Magdics, Marietta
Abstract : Aims: Our initiative - 'Pause, Power Up, Push On (PPP)', closely mirrors the themes of this year's RCPCH conference - 'Connect, Energise, Inspire'. We focused on encouraging teams to connect and celebrate together, both through the challenges of the pandemic, and far beyond. During the first two months of the pandemic alone, a UK Parliament study showed that 50% of NHS staff felt their mental health had declined. This emphasised the importance of wellbeing in the workplace and supporting each other. The PPP initiative focused on positivity and wellbeing for all staff. A hard-working, driven and conscientious workforce strives to provide the optimal care for all patients, however the aim of our initiative was to ensure that working conditions for staff were optimised too - encouraging all staff to actively 'take a break' during their working day. The initiative aimed to catalyse a 'change in culture' across the Trust: To empower teams to take a break together during the working day To boost morale through promoting balanced working environments To enhance team spirit across the multidisciplinary team Methods: A Quality Improvement Model was used to implement the PPP initiative. A 'Rooftop Rota' enabled every specialty to take at least one thirty minute break during the week, using the 'Rooftop Garden', (in line with the social-distancing guidance). Departments were able to 'tick' their attendance and encouraged to take photos, promoting inter-specialty competition. The PPP logo and slogan were created - designed to be memorable and eye-catching ( figure 1 ). This was shared through posters, screensavers and pin badges. Presentations were delivered at forums including Senior Management Leadership, Workforce Leads, Junior Doctor Forum, and individual departmental meetings - encompassing staff groups of different seniorities, specialties and disciplines. Emphasis was placed on involving senior management in encouraging their teams to partake in the initiative, as well as inclusion of all members of staff, including non-clinical. Results: An initial questionnaire demonstrated that 27% of staff never take a break during the working day. The PPP initiative was piloted for a period of two months to improve this, evidenced by attendance on the rooftop, photos and distribution of follow-up questionnaires. There was overwhelmingly positive feedback for the initiative, with participants describing it to be 'Refreshing' and 'Loved time engaging with others'. 76.9% of participants reported that they valued the initiative, with requests for it to be continued. Conclusion: PPP demonstrated that staff have great enthusiasm for incorporating team breaks into their regular working day, and the initiative has been handed over to new team members, to ensure its sustainability. The initiative has also highlighted departments which have not been able to participate, and can prompt further investigation into the hurdles they may be facing. PPP illustrates that despite the challenges we face, through supporting each other, we can continue to shine together.